THE APPLICATION OF PICTURE WORD INDUCTIVE MODEL (PWIM) TO IMPROVE STUDENTS’ ACHIEVEMENTS IN WRITING DESCRIPTIVE TEXT - Jernih D Sinurat (Universitas Potensi Utama, 2019)
This study attempted to investigate the application of picture word inductive model (PWIM) to improve students’ achievements in writing descriptive text. The purpose of the study is to find out whether PWIM can improve students’ achievement in writing descriptive. This study was conducted by applying classroom action research. The subject of this study was the first year students ( X/A) of SMA Swasta Gajah Mada Medan. The data of this research were obtained in two cycles. The instrument used for collecting data was quantitative and qualitative. Based on the writing test result, the students’ score kept improving every test. The findings indicate that the using of PWIM as a media of learning improved students’ writing achievement. The students’ score significant improvement, the mean of second cycle i.e. 80.28 is higher that the mean of the first cycle i.e. 70.86. Based on diary notes, questionnaire sheet, observation sheet and interview, it was found that teaching learning process ran well. The conclusion is that the using of PWIM as a media of learning improves students’ writing Achievement.